Performance Evaluation of 4G LTE Networks Based on QoS Parameters at 2100 MHz and 2300 MHz Frequencies - Asma Amaliah; Alfin Eka Riyanto; Kurniawan Harun; Sukriyah Buwarda; Mardhiyah Nas (Journal of Electrical Engineering and Informatics, 2026)
Objectives: This study aims to evaluate and compare data service performance of 4G LTE networks operating on the 2100 MHz (L2100) and 2300 MHz (L2300) frequency bands utilized by Indonesian mobile network providers, particularly Telkomsel. Methods: Field measurements were conducted at four purposively selected Base Transceiver Station (BTS) locations representing high-traffic urban environments in Makassar, Indonesia. At each BTS, speed tests were repeated five times per session across three different time periods, morning, afternoon, and evening, to ensure data reliability and minimize temporal bias. Packet loss was assessed using a dedicated network diagnostic application under real-world conditions. A total of 60 measurement sessions were recorded across all sites. Results: The L2300 band demonstrated superior throughput, achieving 49.7 Mbps at BTS UPD263 DMT ISAT Kassi-Kassi and 46.8 Mbps at BTS UPD057 MSC Pengayoman. The L2100 band yielded lower speeds of 34 Mbps at BTS UPD172 Kisel and 27.6 Mbps at BTS UPD248 Protelindo Baitul Rahman. Both bands maintained 0% packet loss across all measurement sessions. Novelty: This study contributes empirical, multi-temporal comparative data on 4G LTE performance across two frequency bands within Indonesian urban telecommunications infrastructure, providing actionable insights for network optimization and frequency band selection strategies.